2011
DOI: 10.1007/s11274-011-0671-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis on the diversity of Auricularia auricula-judae by physiological characteristics, somatic incompatibility and TRAP fingerprinting

Abstract: Phenotypic traits (physiological characteristics and somatic incompatibility) and genotypic traits (target region amplification polymorphism TRAP) were used to study the diversity of 32 main cultivars of Auricularia auricula-judae in China. Twenty seven important and stable physiological indexes were evaluated; somatic incompatibility test (SIT) reaction was described from three aspects: type, pigment, and intensity; 16 pairs of TRAP primer combinations produced 535 unambiguous and reproducible DNA fragments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The surface wrinkles (also known as veins) have been described as one of the major features of fruiting bodies 6–8 . The number and depth of wrinkles were deployed for cultivar identification purposes in China 7 . The physiological function of the wrinkles is to be determined although possibilities on reflecting nutrition and quality are widely implicated in the food market.…”
Section: Introductionmentioning
confidence: 99%
“…The surface wrinkles (also known as veins) have been described as one of the major features of fruiting bodies 6–8 . The number and depth of wrinkles were deployed for cultivar identification purposes in China 7 . The physiological function of the wrinkles is to be determined although possibilities on reflecting nutrition and quality are widely implicated in the food market.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other marker techniques, TRAP has the advantages of simplicity, high stability and repeatability, especially preferential targeting and appropriate polymorphism information [15,16]. The effectiveness of the TRAP marker system in determining genetic diversity is reported in wheat [17][18][19][20][21][22], sunflower [9,23,24], lettuce [25], common bean [26], sugarcane [27], spinach [28], faba bean [29], Lentinula edodes [30], Auricularia auricula-judae [15] and pea [31]. Hu et al [25] reported that TRAP markers were able to differentiate 53 lettuce cultivars which were very similar in terms of horticultural properties and types.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of strains are very important for the production output and quality of the cultivated mushrooms. Molecular markers can directly reflect the genetic polymorphisms in DNA levels and have been widely used to analyze the genetic diversities, construct the genetic linkage maps, identify strains, and assist in breeding [ 8 , 9 ]. In the previous studies, the amplified fragment length polymorphism (AFLP) markers and sequence characterized amplified region (SCAR) markers were developed to discriminate the strains and analyse the genetic divergences among the strains of H. marmoreus [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other marker techniques, TRAP has the advantages of easy operation, high stability and repeatability, strong targeting ability, and rich polymorphism information [ 16 , 17 ]. It had been used to analyze the genetic diversity of Lentinula edodes [ 18 ], construct the genetic linkage map of Lentinula edodes [ 9 ], and analyze the relationship between phenotypic and genotypic traits of Auricularia auricula-judae [ 8 ]. However, it has not been applied in H. marmoreus .…”
Section: Introductionmentioning
confidence: 99%